Exsolution Modeling and Control to Improve the Catalytic Activity of Nanostructured Electrodes. Issue 16 (10th March 2023) - Kim, Yo Han; Jeong, Hyeongwon; Won, Bo‐Ram; Myung, Jae‐ha
Abstract: In situ exsolution for nanoscale electrode design has attracted considerable attention because of its promising activity and high stability. However, fundamental research on the mechanisms underlying particle growth remains insufficient. Herein, cation‐diffusion‐determined exsolution is presented using an analytical model based on classical nucleation and diffusion. In the designed perovskite system, the exsolution trend for particle growth is consistent with this diffusion model, which strongly depends on the initial cation concentration and reduction conditions. Based on the experimental and theoretical results, a highly Ni‐doped anode and an electrochemical switching technique are employed to promote exsolution and overcome growth limitations. The optimal cell exhibits an outstanding maximum power density of 1.7 W cm −2 at 900 °C and shows no evident degradation when operating at 800 °C for 240 h under wet H2 . This study provides crucial insights into the developing and tuning of heterogeneous catalysts for energy‐conversion applications. Abstract : Diffusion‐determined exsolution behavior and its mechanism are demonstrated by controlling and modeling particle growth. Following this model, a highly active and durable nanostructured electrode for solid oxide fuel cells using an in situ exsolution method is developed. The particle growth of the exsolved Ni nanoparticles is enhanced by electrochemical switching, leading to a drastic improvement in cell performance.